2016
DOI: 10.1177/1048291116662997
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning a Participatory Health Study for a French Industrial Context

Abstract: The Marseille, France, metropolitan area is home to a heavily concentrated industrial region directly adjacent to residential communities. These towns have been subjected to a wide variety of social science and public health studies, but residents continue to have many questions about health concerns for which they currently have primarily anecdotal evidence. Reflecting on our in-progress research in two of these towns, we argue that community-based participatory research that draws from both social science an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…However, local residents can have differing observations regarding the health and environmental impact of these facilities in the communities, but, without science to back them up, they have a difficult time being heard or their observations taken seriously. This lack of relevant science, or “undone science” ( Hess 2016 ), can underlie power differentials between citizens and corporations or government and can be due to institutional norms and disciplinary practices ( Allen et al 2016 ), but the result is the same—no science answering the citizens’ questions.…”
Section: Emerging Forms Of Knowledge Justice: a Constellation Of Ideamentioning
confidence: 99%
See 1 more Smart Citation
“…However, local residents can have differing observations regarding the health and environmental impact of these facilities in the communities, but, without science to back them up, they have a difficult time being heard or their observations taken seriously. This lack of relevant science, or “undone science” ( Hess 2016 ), can underlie power differentials between citizens and corporations or government and can be due to institutional norms and disciplinary practices ( Allen et al 2016 ), but the result is the same—no science answering the citizens’ questions.…”
Section: Emerging Forms Of Knowledge Justice: a Constellation Of Ideamentioning
confidence: 99%
“… 12. For an in-depth discussion of the interdisciplinary methodology and the specifics of translating CBPEH to a French context, see Allen et al (2016 ). …”
mentioning
confidence: 99%
“…The social integration of knowledge via collaborative analysis leads to a stronger and more relevant report compared to socially remote knowledge that is contained in official state studies or regulatory permitting documents [14]. It is counter to regulatory science that often does not speak to lay-people and the ways in which they live and navigate their neighborhoods and places of work.…”
Section: Discussionmentioning
confidence: 99%
“…Citizen frustration grew from the lack of relevant information. A petition requesting health data was circulated garnering more than 4000 signatures and several dozen residents participated in a sit-in at the French health service’s regional offices, only to be escorted off the property by riot police (for more details, see Allen et al [14]). Our phase one study revealed numerous chronic illnesses that were much higher than the French population.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the local population had suspicions about illnesses in their community, only to be told otherwise by state officials (Allen 2003(Allen , 2014. In the case of France there were no less than a dozen environmental health studies conducted for the benefit of the local residents living in the Étang de Berre industrial region, all showing there was little cause for concern or that there was too much uncertainty in the results such that more studies needed to be done (Allen et al 2016). There were no studies verifying the illnesses that the local residents and their doctors saw on a regular basis.…”
Section: Contextualizing Data: From Health Statistics To Residents' Smentioning
confidence: 99%